Who wants to redistribute? : Russia's tunnel effect in the 1990s - Ravallion, Martin, 1952- 1952- (Policy research working paper, 1999)
Attitudes toward redistribution of wealth in Russia tend to reflect expectations of future mobility, in both directions. Few Russians expected rising living standards in the 1990s, and most expected a decline in living standards, so there was strong demand for redistribution, even among those currently well off but fearful of the future